Assessing the Role of Trust in Merchant Adoption of Mobile Payments in Ghana - Yeboah, E.; Boateng, R.; Owusu, A.; Afful-Dadzie, E.; Ofori-Amanfo, J. (International Federation for Information Processing, 2020)
Encouraged by the crucial need to understand merchant adoption of mobile payment, this study explores the role trust play in the adoption of mobile payment by merchant and the enablers for merchant’s trust in mobile payment systems. This was done by Conceptualising the characteristics of the service provider and technology characteristics as the two dimensions that could influence merchant adoption of mobile payments. The study was done through the lenses of the Technology Acceptance Model (TAM) and the Trust-Theoretic Model and adopted a qualitative approach where two merchants were selected from the health sector. The findings demonstrate that the role of merchant trust is very critical for adoption due to m-payment technology and security risk. Hence, sufficient trust-building structures in mobile payment space are essential for the adoption of mobile payment by merchants. Moreover, the findings indicate mobile service provider characteristics and the mobile technology characteristics are both imperative toward building trust in mobile payment systems for merchants’ adoption. The study also found that the trust of both technology and service provider has a far more critical influence on merchants’ adoption of mobile payments than perceived usefulness or ease of use. The study, therefore, recommends that service providers should consider the opportunity to nurture merchant trust because merchant trust acts as a fundamental enabler for the adoption of mobile payments. Other implications are also discussed.
Research Article
Keywords: Merchants; Adoption; M-payments; Trust; Ghana